Phytosociological remarks on residual woodlands of Laurus nobilis in Sicily - Gianguzzi, Lorenzo; D’Amico, Agostino; Romano, Salvatore (Lazaroa, 2011)
A phytosociological study was done of Laurus nobilis woodlands in Sicily. The analysis, based on 18 releves, supports the definition of a new syntaxon (Acantho mollis-Lauretum nobilis ass. nov.), considered as a vicariant of similar vegetation aspects described in other Mediterranean areas (Iberian and Italian peninsulas). The study mainly includes some unpublished sites where polycormic individuals of laurel, sometimes reaching 13-15 meters in height, dominates the tree layer. This vegetation is also characterized by some laurophyllous species (Hedera helix, Rhamnus alaternus, Smilax aspera and sometimes Viburnum tinus) and lianas (Rubia peregrina var. longifolia, Asparagus acutifolius, Tamus communis, Clematis vitalba, Calystegia sylvatica and Rubus ulmifolius), while in the undergrowth comprises particularly various broadleaved elements such as Cyclamen hederifolium subsp. confusum, and Acanthus mollis subsp. mollis, both included in the characteristic species combination together with Pistacia terebinthus and Orobanche hederae. The coenosis is typical of the humic soils, often rich in lithic components, of shaded ravines and peririparian environments, in the thermo- and mesomediterranean thermotype (Mediterranean pluviseasonal oceanic bioclimate). In view of the relictual status of this vegetation - also included as a "Priority Habitat" in Council Directive 92/43/EEC - we underline the need for a suitable protection and conservation of these small, fragmented and isolated patches.